Microbial Qualities of Nkwuaku and Ogbaru Streams Located in Awgu Local Government Area in Enugu State, Nigeria - Osita Gabriel Appeh; Tochukwu Frank Egwuatu; Chiamaka Maryann Ogbunta (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Water samples from Nkwuaku and Ogbaru streams located in Awgu local government area in Enugu State, Nigeria were evaluated for the presence of microbial contaminants. Both samples were subjected to physicochemical analysis, total bacterial count and isolation of microbial pathogens, using conventional techniques. Physicochemical characteristics of both water samples showed that Nkwuaku stream had the least total dissolved solid value of 210mg/L while the highest value of 270mg/L was recorded for Ogbaru stream. Total heterotrophic bacteria count revealed that Ogbaru stream water sample had a higher bacterial population of 5.1x107cfu/ml than Nkwuaku stream water sample which had a bacterial population of 4.2x107cfu/ml. A total number of twelve (12) microorganisms were isolated from both water samples analyzed. Eight (8) bacteria genera isolated include: Escherichia coli, Enterococcus faecalis, Salmonella spp., Klebsiella spp., Staphylococcum aureus, Pseudomonas aeruginosa, Proteus spp. and Campylobacter spp. Four (4) fungi were isolated and they include: Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus and Fusarium oxysporum. Escherichia coli, Salmonella spp., Staphylococcus aureus and Proteus spp. had the highest percentage occurrence (16.66%) each while Enterococcus faecalis, Klebsilla spp., Pseudomonas aeruginosa and Campylobacter spp. had the least percentage occurrence (8.33%) each. Also, Aspergillus recorded the highest percentage occurrence of 40% for fungi while the least percentage (20%) was recorded for Aspergillus niger, Fusarium oxysporium and Aspergillus fumigatus each. This study reveals that microbial qualities of these streams render them unfit for human consumption as sources of portable water although they can be used for other household purposes.